Luminescence characteristics of Al-and Ca-doped BeO obtained via a sol-gel method. (August 2019) - Altunal, V.; Guckan, V.; Ozdemir, A.; Can, N.; Yegingil, Z.
Abstract: BeO, BeO:Al1%, BeO:Ca1%, and BeO:Al1%, Ca0.1% ceramics were synthesized by the sol-gel method. The X-ray luminescence was studied, and broad emission peaks located at 230 nm (∼5.4 eV) and 300 nm (∼4.1 eV) were observed. We investigated thermoluminescence peaks contributing to optically stimulated luminescence (OSL) signals for the ceramics. The thermal quenching of the OSL signals was evaluated, and the quenching energies were estimated as between approximately 0.5 eV and approximately 0.7 eV. To check the feasibility for dosimetry purposes, the dose response, reusability, and dark storage fading of the OSL signals were investigated. The dose response was observed to be linear between 0.1 and 100 Gy. The minimum detectable doses of BeO, BeO:Al1%, BeO:Ca1%, and BeO:Al1%, Ca0.1% were estimated as approximately 0.9 mGy, approximately 4 mGy, approximately 0.5 mGy, and approximately 0.5 mGy, respectively. Very good reusability was observed over ten cycles, with a maximum deviation of 2%. The results obtained from BeO:Al1%, Ca0.1% could be useful for OSL dosimetry, particularly in medical applications. Highlights: The synthesis and doping of BeO powders using the sol-gel method. The influence of the dopant on the structural and morphological properties of BeO ceramic pellets. The effect of the dopant on optically stimulated luminescence dosimetric properties of BeO ceramic pellets. Evaluation of thermal quenching energies for Al- and Ca-doped BeO ceramic pellets. The relationship between thermoluminescence and optically stimulated luminescence signals from doped BeO ceramic pellets.